The biogenesis, biological functions and modification of Circular RNAs - Liu, Sen; Guo, Xiang Yu; Shang, Qing Juan; Gao, Peng (Experimental and molecular pathology, 2023)
Circular RNAs are covalently closed and non-coding in eukaryotes, which have tissue- specific and temporal-specific expression patterns whose biogenesis is regulated by transcription and splicing. Most circular RNAs are localized in the cytoplasm. The sequences and protein-binding elements of circular RNAs facilitate circular RNAs in exerting biological functions through complementary base pairing, regulating protein function or self-translation. Recent studies have revealed that N6-Methyladenosine (m6A), a prevalent post-transcriptional modification, can affect the translation, localization, and degradation of circular RNAs. Cutting-edge research into circular RNAs have benefitted from the development of high-throughput sequencing technology. Furthermore, the expansion of novel research methods has promoted progress into circular RNA research.